Long term adaptation of a microbial population to a permanent metabolic constraint: overcoming thymineless death by experimental evolution of Escherichia coli - de Crécy-Lagard, Valérie A (BioMed Central, 2001)
BACKGROUND: To maintain populations of microbial cells under controlled conditions of growth and environment for an indefinite duration is a prerequisite for experimentally evolving natural isolates of wild-type species or recombinant strains. This goal is beyond the scope of current continuous culture apparatus because these devices positively select mutants that evade dilution, primarily through attachment to vessel surfaces, resulting in persistent sub-populations of uncontrollable size and growth rate. RESULTS: To overcome this drawback, a device with two growth chambers periodically undergoing transient phases of sterilization was designed. The robustness of this device was assessed by propagating an E. coli strain under permanent thymine starvation for over 880 days, i.e. metabolic conditions notoriously known to lead to cell death and clogging of cultivation vessels. Ten thousand generations were required to obtain a descendant lineage that could resist thymine starvation and had recovered wild-type growth rate. CONCLUSIONS: This approach provides a technological framework for the diversification and improvement of microbial strains by long-term adaptation to inescapable metabolic constraints. An E. coli strain that is totally resistant to thymineless death was selected.